Analysis of pedestrian gap acceptance behavior at unsignalized mid-block crossing under mixed traffic conditions - Satanan Piyalungka; Kunnawee Kanitpong; Ampol Karoonsoontawong; Santoso, Djoen San; His Majesty the King{u2019}s Scholarships (Thailand) (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
In developing countries, the safety of pedestrians is a crucial concern, especially as they are at a higher risk of accidents. The objective of this research is to analyze the critical gap and dilemma zone for pedestrians crossing unsignalized mid-block crosswalks in Bangkok, Thailand, utilizing Raff's and logit methods. Data from video graphics surveys were analyzed using multiple linear regression and binary logit models to identify factors affecting accepted gap size and gap acceptance behavior. The findings indicate that critical gaps and dilemma zones differ for two-lane and four-lane road sections, and several factors such as yielding behavior, waiting time, age, and crossing speed of pedestrians, and vehicle speed and type influence gap acceptance. The study emphasizes the need to consider pedestrians' vulnerability and behavior to improve safety at crosswalks in developing nations. This research contributes to the existing literature on pedestrian safety and provides insights for policymakers and urban planners to design safer crosswalks.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Transportation Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 2023
Keywords: Pedestrians -- Thailand -- Bangkok; Pedestrian crosswalks -- Thailand -- Bangkok